2014
DOI: 10.1055/s-0034-1370346
|View full text |Cite
|
Sign up to set email alerts
|

Severe Liver Injury while Using Umbilical Venous Catheter: Case Series and Literature Review

Abstract: In all neonates with liver injury, UVC was malpositioned within the portal circulation. Despite the fact that our report provides only circumstantial evidence for the mechanism of injury, it supports reports which suggest that "low" UVC position increases potential for this type of complication. Acute onset of abdominal distension in a neonate with UVC should prompt ultrasonographic evaluation of position of the catheter tip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 22 publications
1
43
1
3
Order By: Relevance
“…The complications associated with malpositioned UVC include pericardial effusion, cardiac tamponade,5 6 pleural effusion,7 8 thrombosis,9 10 cardiac arrhythmias,11 endocarditis,12 liver haematoma,13 diffuse liver injury14 and portal hypertension 15…”
Section: Introductionmentioning
confidence: 99%
“…The complications associated with malpositioned UVC include pericardial effusion, cardiac tamponade,5 6 pleural effusion,7 8 thrombosis,9 10 cardiac arrhythmias,11 endocarditis,12 liver haematoma,13 diffuse liver injury14 and portal hypertension 15…”
Section: Introductionmentioning
confidence: 99%
“…Our literature review revealed that risks are associated with both central 12,14,26 and low-lying UVC positioning. 4,25,31,34 There is little guidance, however, on how the UVCs should be used.…”
Section: Discussionmentioning
confidence: 99%
“…In einer retrospektiven Studie an 210 Frühgeborenen mit einem Geburtsgewicht < 1250 g betrug die Rate an Pfortaderthrombosen 10 % und in einer weiteren Analyse an 109 Früh-und Reifgeborenen sogar 43 % [25]. Hauptrisikofaktoren sind ▪ die NVK-Malposition, d. h. eine zu kaudale und nicht-zentrale Katheterposition, ▪ eine ungewöhnlich lange Katheterliegezeit und ▪ die Infusion von Blutprodukten [17,18,26].…”
Section: Thrombose Und Nabelvenenkatheterunclassified